2016
DOI: 10.1002/adfm.201504172
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the High‐Temperature Chemical Synthesis of Magnetic Nanoparticles

Abstract: Depending on the solvent chosen, high temperatures can be used to control metal precursor reaction and the formation of magnetic NPs. It is versatile in controlling NP size, shape, structure and composition. [ 7 ] In this chemical context, two methods are commonly used. The fi rst one relays on the rapid injection of the reagents, which are often organometallic compounds, into hot surfactant solution, inducing the simultaneous formation of many nuclei ( Figure 1 ). Alternatively, reducing agents can be quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…Healthcare Mater. 2017, 6,1700306 restrictions is exerted by the body, nanoparticles with narrow size distribution range near to the optimum size and shape will be drastically required to prevent their filtration from the bloodstream. On the other hand, surface properties of MNPs such as surface charge and hydrophobicity play an important role in defining their biological identity within the body.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare Mater. 2017, 6,1700306 restrictions is exerted by the body, nanoparticles with narrow size distribution range near to the optimum size and shape will be drastically required to prevent their filtration from the bloodstream. On the other hand, surface properties of MNPs such as surface charge and hydrophobicity play an important role in defining their biological identity within the body.…”
Section: Resultsmentioning
confidence: 99%
“…[300] In the case of fungi-mediated biosynthesis of magnetite nanoparticles, up to our knowledge, there is only one study performed by Bharde et al [301] Within this elegant study, magnetite nanoparticles with appropriate stoichiometry were produced by challenging F. oxysporum and Verticillium sp. with an aqueous solution containing a mixture of ferricyanide [Fe(CN) 6 ] 3+ ions and ferrocyanide [Fe(CN) 6 ] 4+ ions. TEM images of the resultant magnetite nanoparticles revealed that magnetite nanoparticles of quasi-spherical shape in the 20-50 nm size range were synthesized by F. oxysporum, while verticillium sp.…”
Section: Fungi Mediated Synthesis Of Magnetite Nanoparticlesmentioning
confidence: 99%
“…Zero‐valent iron nanoparticles are relevant in regard of different aspects ranging from fundamental science to potential application. First of all, Fe(0) is well‐known for its ferromagnetic properties and in the case of spherical nanoparticles specifically for its superparamagnetism, which can be used for soft magnetic applications as well as magnetic liquids . Fe(0) is an essential constituent of prominent organometallic compounds such as iron carbonyls (e.g., Fe(CO) 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…First of all, Fe(0) is well-known for its ferromagnetic properties and in the case of spherical nanoparticles specifically for its superparamagnetism, [1] which can be used for soft magnetic applications as well as magnetic liquids. [2] Fe(0) is an essential constituent of prominent organometallic compounds such as represents a straightforward one-pot approach and is performed in the absence of any oxygen source (e.g., starting materials, solvents, stabilizers). As a result, uniform Fe(0) nanoparticles with a size of 3-5 nm and high purity were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The most common synthetic methods for creating functional IO NPs (i.e., the co-precipitation method by Massart [ 28 ], and the solvothermal method by Sun [ 29 ]) yield quasi-spherical particles or IO cubes in the range of tens of nanometers or smaller. While there are numerous papers that describe methods for creating non-spherical IO nanostructures [ 30 ] (particularly wires [ 23 , 31 ], rods [ 32 , 33 , 34 , 35 , 36 ], cubes [ 37 , 38 , 39 ], and sheets [ 40 ]), fewer of those are used or investigated for in-depth (bio)medical research. While there is a wealth of data for T2 MRI contrast enhancement and magnetic hyperthermia use of such IO nanoshapes [ 41 ], specific cell uptake [ 42 ] in various relevant tissue or cancer cell lines as well as their intracellular behavior have remained, to a large extent, unexplored.…”
Section: Introductionmentioning
confidence: 99%